Justification by Faith and Justification by Works: Martin Luther and Modern Ethics - HE Huaihong, (Journal of Research for Christianity in China (JRCC), 2025)
In the first half of the 16th century, Martin Luther initiated the Reformation with the spirit of “justification by faith.” In the latter half of the 20th century, John Rawls' influential theory of justice exhibited a characteristic of “justifying apart from faith.” These two thinkers, representing opposite ends of the spectrum, expressed markedly different views on the respective contents and interrelationship of faith and morality, reflecting the distinct eras, societies, and personal life experiences they traversed. Now, the five centuries of most profound and rapid transformation in human history have passed. From the perspective of modern ethics, reviewing this trajectory of intellectual evolution; analyzing and comparing how the content and relationship between “faith” and “justice” were evoked and articulated by these two thinkers, revealing their intertwined nature and the complexities and challenges they entail; and exploring whether these two perspectives can be balanced and reconciled within certain limits and parameters—all hold profound significance for how people in modern society navigate the relationship between faith and morality.
Keywords: Faith Morality Reformation Modern Ethics